Russian higher education problems through the comparative analysis and contraposition of representations of university teachers and students (Part II) - Galina I. Saganenko; Aleksey A. Sidorin; Elena I. Stepanova (Высшее образование в России)
The second part of the article focuses on finding the specific features of a social situation with Russian higher education through the representations of university teachers and students. The preceding publication analyzed the full arrays of the articles titles of the journal «Higher Education in Russia» relating to 2011 and to 2012. The given article draws the additional resource – the data arrays received from the students polls. The significant problems of Russian education are treated through the comparative analysis and contrapositions of the conceptions of university teachers and students.The work was carried out with information arrays within the analytical modules of the“VEGA” computer program.